EFEKTIVITAS Trichoderma virens DALAM MENGENDALIKAN Ganoderma boninense DI PRE NURSERY KELAPA SAWIT PADA MEDIUM GAMBUT - YUSMAR MAHMUD; CINDY ROMANTIS; SYUKRIA IKHSAN ZAM (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2020)
Palm oil production in Riau continues to increase from year to year. The increase in palm oil production still has obstacles caused by pests and diseases, among others caused by pathogenic fungi, Ganoderma boninense, this fungus causes root rot disease. Control of stem rot disease is needed appropriate techniques, especially controls that are environmentally friendly. One of the uses of biological agents, such as Trichoderma, especially Trichoderma virens. This study aims to obtain a dose of Trichoderma virens that is effective in controlling Ganoderma boninense in oil palm pre nursery on peat medium. This research was conducted at the experimental field of the Faculty of Agriculture and Animal Husbandry of the State Islamic University of Sultan Syarif Kasim Riau. This research was conducted in December 2018 - March 2019. This research was a field experiment (experiment) using a Non Factorial Completely Randomized Design (RAL) by conducting Trichoderma virens test on oil palm seeds with various doses where each treatment was repeated 6 times there are 30 experimental units. The results showed that the parameters observed were macroscopic and microscopic fungi ,in-vitro test, speed of infection, intensity of disease attack, plant height, stem diameter and root root ratio. The results showed that Trichoderma virens fungi can reduce the intensity of fungal disease attack Ganoderma boninense given Trichoderma virens increased the growth of stem diameter of oil palm seedlings.